La edición facsímil digital en la biblioteca virtual Miguel de Cervantes - Martínez Poveda, Paloma; Pérez Barroso, Raquel; Villar Rodríguez, Jorge Carlos (Revista General de Información y Documentación, 2005)
The facsimile digital edition is one of the departments in the Miguel de Cervantes Digital Library. This project was born in the University of Alicante in 1999. From this department we try to recover printed texts and manuscripts which have a difficult access. Also our intention is to take the advantage of the new technologies to give a great spreading of this kind of works, as well as to contribute to their preservation. As we can check, the digital edition department tries to offer cared editions, with index of contents, as well as very useful tools for the researchers, as crossing links. In this article we will see all kind of originals we use (original books or manuscripts, microfilms, facsimile editions, slides...), the used ways to get the digital pictures, the outcome in Internet, the chosen solutions for getting a better accesibility, the advantages of this kind of edition and the didactic applications.